(untitled) (Journal of Hama University, 2020)
This research aimed to study the extent of mobile phone use by farmers and the most important areas and methods of its use, as well as the correlation between the personal and social characteristics of farmers and the extent of their use of mobile phone, through a random sample of 150 farmers randomly selected from a number of villages belonging to the results of the analysis of the research sample showed that the largest percentage of the sample is middle-aged (44%), and that 42% of the sample hold a basic education certificate, The results also showed that (64.7%) of the sample work in the field of plant production especially rain fed, and the largest proportion of farmers (30%) their annual income ranges between 500001 and 710000 SP, the average farm area 31 dunums, and 51.3% of the sample is available In their villages, extension units, 85.3% of the sample have a landline phone, 77.3% have modern mobile phones, and 50.7% do not have internet access at home. As for the methods of using a mobile phone, it was noted that its use is still limited to sending and receiving messages The rate of its use was between medium and large (86%), It was associated with the age of the farmer and his educational level, the presence of the extension unit in the village and the presence of Internet service at home significantly.